Ready display of antigenic peptides in a protein 'mimogen'. - Vallée, M; Schombs, M; Balaban, Z; Colyer, J; Davis, B (Royal Society of Chemistry, 2016)
Given the dependence of much modern biology upon the use of antibodies as tools and reagents, their variability and the often associated lack-of-detail about function and identity creates experimental errors. Here we describe the proof-of-principle for a potentially general, versatile method for the display of antigens in a soluble yet standard format on a lateral protein scaffold that mimics normal epitopes in a protein antigen (a 'mimogen') and confirm their utility in phosphorylation-dependent recognition by specific antibodies.